Exact Transient Analysis of a Biconical Antenna of Arbitrary Length and Cone Angle - Janaswamy, Ramakrishna (IEEE transactions on antennas and propagation, 2023)
Starting from a new factorization of the frequency-domain modal expansion coefficients, we generate analytical expressions in the time domain for the various quantities of interest of a biconical antenna of arbitrary length and cone angle. In particular, expressions are generated for the impulse response of the feed current and the radiated fields as well as the transient effective length. Comparison with measured results available in the literature is carried out for the antenna's effective length. The response due to any other feed voltage pulse can be obtained in terms of the impulse response via convolution. Results are presented for a Gaussian and a fast-rising feed voltage pulse. For the fast-rising feed voltage pulse, the transient radiated energy density is shown to decay less rapidly than as inverse square distance over significant distances from the antenna. The expressions presented in this article are all general and exact and not subject to any analytical approximations.